Selected Abstracts of the 19th National Congress of the Italian Society of Perinatal Medicine (Società Italiana di Medicina Perinatale, SIMP); Naples (Italy); January 19-21, 2017 - - (Hygeia Press di Corridori Marinella, 2017)
Selected Abstracts of the 19th National Congress of the Italian Society of Perinatal Medicine (Società Italiana di Medicina Perinatale, SIMP); Naples (Italy); January 19-21, 2017   Guest Editors: Irene Cetin, Mariavittoria Locci   ABS 1. THE "WOMAN AND CHILD HOSPITAL" ORGANIZED ON INTENSITY OF CARE IN VERONA: AN OPPORTUNITY TO PROMOTE MATERNAL AND PERINATAL HEALTH • C. Bovo, R. Bortolus, G. Ghirlanda, P. Biban, V. Bergamini, A. Bonetti, E. Allegrini, G. Piacentini ABS 2. CIRCULATING LEVELS OF NATURAL KILLER T CELLS AND ENDOTHELIAL PROGENITOR CELLS IN PRE-ECLAMPTIC PREGNANT WOMEN • E. Piccione, F. Basile, A. Santamaria, L. Rizzo, D. Giordano, S. Loddo, R. D'Anna ABS 3. CLASSIFICATION OF THE RISK FACTORS FOR STILLBIRTH FOLLOWING THE IMPLEMENTATION OF A CLINICAL AUDIT METHOD: PRELIMINARY DATA FROM A WIDE AREA IN NORTHERN ITALY • A. Ferretti, L. Galli, A. Dall'Asta, S. Fieni, T. Frusca ABS 4. CESAREAN SECTION: INDICATIONS AND INCIDENCE IN THE LAST DECADES • L. Rizzo, F. Basile, A. Santamaria, R. D'Anna ABS 5. MATERNAL NEAR MISS: A 10-YEAR SURVEILLANCE STUDY IN A TERTIARY CARE FACILITY OF NORTHERN ITALY • G. Zanconato, C. Bovo, E. Cavaliere, R. Bortolus, R. Castellani, M. Franchi ABS 6. IS LENTICULOSTRIATED VASCULOPATHY AT HEAD ULTRASOUND AN UNFAVORABLE PROGNOSTIC FINDING IN PATIENTS WITH CONGENITAL CYTOMEGALOVIRUS INFECTION? • A. De Matteis, A. Giannattasio, P. Di Costanzo, P. Milite, D. De Martino, M.R. Augurio, C. Grande, E. Capone, A. Romano, F. Raimondi ABS 7. MATERNAL IMMUNOSUPPRESSION AND RISK OF SEVERE CONGENITAL CYTOMEGALOVIRUS INFECTION • A. De Matteis, A. Giannattasio, S. Cenni, L. Bucci, P. Milite, F. Raimondi, P. Di Costanzo ABS 8. NEUROIMAGING STUDIES AND NEURODEVELOPMENTAL OUTCOME IN A LARGE COHORT OF INFANTS WITH CONGENITAL CYTOMEGALOVIRUS INFECTION • C. Grande, M.R. Augurio, D. De Martino, L. Bucci, L. Capasso, P. Di Costanzo, A. Giannattasio, F. Raimondi ABS 9. POSTPARTUM HEMORRHAGE RISK AFTER EXPOSURE TO SSRIs DURING PREGNANCY • S. Corti, P. Pileri, M. Mazzocco, I. di Bartolo, C. Mandò, I. Cetin ABS 10. LONGITUDINAL PHARMACOKINETIC AND PSYCHIATRIC EVALUATION OF PREGNANT WOMEN IN TREATMENT WITH SSRIs • S. Corti, P. Pileri, C. Personeni, A. Colombo, C. Viganò, E. Clementi, I. Cetin ABS 11. NEONATAL OUTCOMES AFTER EXPOSURE TO SSRIs DURING FETAL LIFE: A PHARMACOKINETIC AND PHARMACOGENETIC ANALYSIS • S. Corti, P. Pileri, C. Mandò, L. Pogliani, E. Clementi, D. Cattaneo, I. Cetin ABS 12. PREVENTION OF ADVERSE MATERNAL-PERINATAL OUTCOMES: FROM PROCEDURE TO CLINICAL PRACTICE THROUGH SIMULATIONS FOR THE MANAGEMENT OF EMERGENT CESAREAN SECTION (ECS-RED) • F. Parissone, A. Bianchi, F. Galeone, P. Bonetti, A. Demattè, C. Lazzari, N. Papadopoulos, D. Balestreri ABS 13. A CASE OF NEONATAL CYTOPENIA: A CONGENITAL RUBELLA SYNDROME OR SOMETHING ELSE? • P. Stellato, A. De Matteis, P. Milite, L. Mari, A. Umbaldo, T. Cozzolino, R. Savarese, G. De Simone, P. Di Costanzo, G. Menna, F. Raimondi ABS 14. PLACENTAL GROWTH FACTOR AS A PREDICTIVE MARKER OF PREECLAMPSIA • V. Giardini, R. Rovelli, N. Roncaglia, L. Giunti, P. Algeri, C. Callegari, P. Vergani ABS 15. CLINICAL AUDIT: A WAY TO REVIEW AND IMPROVE OBSTETRICAL PRACTICE RELATED TO CESAREAN SECTION AT S. ANNA HOSPITAL • S. Paracchini, B. Masturzo, D. Tangolo, P. Gaglioti, A. Rolfo, T. Todros ABS 16. MULTIETHNIC POPULATION IN PREGNANCY, A RETROSPECTIVE ANALYSIS • M. Zamarra, M.C. Tonnarelli, I. Giardina, L. Di Fabrizio, G. Babucci, C. Antonelli, G.C. Di Renzo ABS 17. MOSCHCOWITZ SYNDROME IN TWIN PREGNANT WOMEN AFTER OOCYTES DONOR CYCLES: A CASE REPORT • M. Miranda, C. Alviggi, G. Nazzaro, E. Salzano, A. Conforti, M. Locci, G. De Placido ABS 18. POSTPARTUM HEMORRHAGE AND MATERNAL OUTCOMES AFTER UTERINE TAMPONADE "BAKRI BALLOON": OUR EXPERIENCE • M.L. Pisaturo, R.L. Paradiso, M.T. Orlando, F. Rosa, G. Di Pierro, S. Schettini ABS 19. KIND OF PAIN DURING LABOR AND MATERNAL-FETAL EFFECTS OF EPIDURAL ANALGESIA • G. Babucci, A. Righi, A. Favilli, I. Giardina, M. Zamarra, L. Di Fabrizio, E. Laurenti, F. Bavetta, F. Pauselli, C. Antonelli, G.C. Di Renzo ABS 20. DIFFERENT 3D TECHNIQUES IN THE STUDY OF FETAL CORPUS CALLOSUM AND ROLE OF 5D CNS PLUS • E. Salzano, G. Nazzaro, M. Miranda, T. Palmieri, R. Iazzetta, M. Locci ABS 21. EVALUATION OF UTERINE ARTERIES DOPPLER AND ESTROGEN MILIEU IN OOCYTE DONATION PREGNANCIES • L. Mandia, P. Cavoretto, A. Inversetti, P. Duca, I. Cetin, V. Savasi ABS 22. EVALUATION OF HORMONAL MILIEU IN THREE DIFFERENT MODE OF CONCEPTION • E. Grossi, L. Mandia, E. Gjoni, I. Cetin, V. Savasi ABS 23. BREASTFEEDING: BIOLOGICAL AND SOCIAL VARIABLES COMPARED TO MODE OF CONCEPTION • P. Pileri, I. di Bartolo, T. Kind, I. Cetin, V. Savasi ABS 24. LAPAROTOMIC MYOMECTOMY AT 18 WEEKS' GESTATION DUE TO UTERINE FIBROID TORSION DURING PREGNANCY: A CASE WITH SUCCESSFUL SURGERY AND SPONTANEOUS VAGINAL DELIVERY AT TERM • A. Basso, M.R. Catalano, G. Loverro, S. Nocera, E. Di Naro, M.T. Loverro, M. Natrella, S.A. Mastrolia ABS 25. MALPERFUSION WITH EARLY DISTAL VILLOUS HYPOPLASIA: A HISTOLOGICAL LANDMARK OF THE GREAT OBSTETRICAL SYNDROMES • S.A. Mastrolia, L. Resta, A. Basso, M.R. Catalano, F.P. Bianchi, S. Tafuri, N. Laforgia, T.A. Florio, M. Loverro, A. Di Mauro, G. Loverro ABS 26. FAILED VACUUM EXTRACTION - IS IT ASSOCIATED WITH LONG-TERM PEDIATRIC CARDIOVASCULAR, ENDOCRINE, AND INFECTIOUS MORBIDITY OF THE OFFSPRING? • S.A Mastrolia, A. Walfisch, T. Wainstock, D. Landau, E. Sheiner ABS 27. THE ASSOCIATION BETWEEN FAILED VACUUM AND LONG-TERM PEDIATRIC HEMATOLOGICAL MORBIDITY • S.A Mastrolia, A. Walfisch, T. Wainstock, D. Landau, E. Sheiner ABS 28. PERICONCEPTIONAL MATERNAL BIOMARKERS OF ONE-CARBON METABOLISM ARE ASSOCIATED WITH EMBRYONIC DEVELOPMENT ACCORDING TO THE CARNEGIE STAGES: THE ROTTERDAM PERICONCEPTIONAL COHORT (PREDICT STUDY) • F. Parisi, M. Rousian, A.H.J. Koning, S.P. Willemsen, I. Cetin, R.P.M. Steegers-Theunissen ABS 29. MATERNAL DIETARY PATTERNS AND HUMAN PRENATAL CEREBELLAR GROWTH: THE ROTTERDAM PREDICT STUDY • F. Parisi, M. Rousian, I.V. Koning, S.P. Willemsen, J.H.M. de Vries, I. Cetin, E.A.P. Steegers, R.P.M. Steegers-Theunissen ABS 30. NUTRITIONAL STATUS AND ADHERENCE TO MEDITERRANEAN DIET IN WOMEN AFFECTED BY GESTATIONAL DIABETES MELLITUS • A. Spadafranca, C. Pieretti, L. Lewandowski, S. Bertoli, A. Battezzati, E. Ferrazzi ABS 31. THE METALLOME OF HUMAN MATERNAL AND FETAL BLOOD IN GESTATIONAL DIABETES MELLITUS • S. Visentin, V. di Marco, M. Tosato, M. Roverso, M. Calanducci, A. Zanella, V. De Marco, M. Camerin, E. Cosmi ABS 32. BODY MASS INDEX AND SYMPTOMS OF EATING DISORDERS IN BREASTFEEDING WOMEN • F. Volpe, L. Giliberti, F. De Luca, G. Straface, V. Zanardo ABS 33. ASSOCIATIONS BETWEEN MATERNAL PREGESTATIONAL BODY MASS INDEX, ROBSON CLASS AND DELIVERY MODE • I. di Bartolo, M. Musto, F. Parisi, P. Antonazzo, I. Cetin ABS 34. DOES THE STOP OF MEDITERRANEAN DIET INFLUENCE GESTATIONAL WEIGHT GAIN AND PUERPERAL PSYCHOLOGICAL ADAPTATIONS? • L. Giliberti, F. Volpe, R. Maione, M. Bertin, G. Straface, V. Zanardo ABS 35. LIFESTYLE INTERVENTION IN OVERWEIGHT/OBESE PREGNANT WOMEN AND ITS EFFECT ON LARGE FOR GESTATIONAL AGE (LGA) BABIES OCCURRENCE • L. Di Cerbo, B. Petrachi, G. Grandi, E. Petrella, I. Neri, F. Facchinetti ABS 36. THYROID DISEASES AND PREGNANCY • G. Babucci, M. Zamarra, L. Di Fabrizio, E. Laurenti, F. Bavetta, F. Pauselli, C. Antonelli, I. Giardina, G.C. Di Renzo ABS 37. GESTATIONAL WEIGHT GAIN (GWG) AS AN INDEPENDENT RISK FACTOR FOR ADVERSE PREGNANCY OUTCOME IN WOMEN WITH GESTATIONAL DIABETES MELLITUS (GDM): A RETROSPECTIVE OBSERVATIONAL STUDY • F. Macrì, E. Di Pasquo, S. Salvi, D. Pitocco, E. Di Stasio, A. Lanzone, S. De Carolis ABS 38. ACUTE RENAL FAILURE DUE TO MATERNAL EXPOSURE TO ANGIOTENSIN RECEPTOR ANTAGONISTS • E. Bonanno, M. Lucente, A. Contaldo, R. Gualtieri, C.D. Costabile, G. Boscarelli ABS 39. ANTI-RH IMMUNOPROPHYLAXIS AT 28 WEEKS: WHAT EFFECTS ON THE FETUS? • G. Fantappiè, C. Linari, E.R. Magro-Malosso, M. Aldinucci, M. Di Tommaso ABS 40. CORRELATION BETWEEN PLACENTAL HISTOLOGICAL PATTERNS AND ANGIOGENIC FACTORS IN PREGNANCIES COMPLICATED BY HYPERTENSIVE DISORDERS OF PREGNANCY AND/OR INTRAUTERINE GROWTH RESTRICTION • D. Di Martino, L. Avagliano, S. Zullino, D. Casati, V. Sterpi, S. Grimaldi, M. Parasiliti, F. Fusè, G. Bulfamante, E. Ferrazzi ABS 41.